Long-chain alkanes preserved in a Martian mudstone - Caroline Freissinet; Daniel P. Glavin; P. Douglas Archer; Samuel Teinturier; Arnaud Buch; Cyril Szopa; James M. T. Lewis; Amy J. Williams; Rafael Navarro-Gonzalez; Jason P. Dworkin; Heather. B. Franz; Maëva Millan; et al. (Proceedings of the National Academy of Sciences, 2025)
Organic molecules preserved in ancient Martian rocks provide a critical record of the past habitability of Mars and could be chemical biosignatures. Experiments conducted by the Sample Analysis at Mars instrument onboard the Curiosity rover have previously reported several classes of indigenous chlorinated and sulfur-containing organic compounds in Gale crater sedimentary rocks, with chemical structures of up to six carbons. Here, we report the detection of decane (C 10 H 22 ), undecane (C 11 H 24 ), and dodecane (C 12 H 26 ) at the tens of pmol level, released from the Cumberland drilled mudstone sample, using a modified SAM analytical procedure optimized for the detection of larger organic molecules. Laboratory experiments support the hypothesis that the alkanes detected were originally preserved in the mudstone as long-chain carboxylic acids. The origin of these molecules remains uncertain, as they could be derived from either abiotic or biological sources.